Scale-up manufacture and characterisation of resorbable phosphate based glass fibre for textile production - Zhu, Chenkai (2016)
Bioresorbable phosphate-based glasses (PBG) have been investigated for varying tissue engineering applications such as fibrous reinforcement for fully resorbable PLA composite for fracture fixation. The mechanical properties of these composites are determined by the mechanical properties of phosphate glass fibre (PGF) which can be tailored by varying the chemical composition of glass. However, current phosphate glass fibre production is in lab-scale quantities and in single filament form which limits the use of these fibres as they can only be produced as non-woven random or unidirectional fibre mats.